(3GdGJUGd GdLeGgjQj Hjf GdGYdGe h GdJWhjY h GdJfejI (B. /s - (3HOQ, CMeOs ((3GdbGgQI (B:s (3OGQ bHGA ddWHGYI h GdfTQ h GdJhRjY ,s, 1998)
(3Ef eMGhdI GdSjWQI aj Ybd GdEfSGf h Sdhcg gh eMhQ GdCSGdjH GdGJUGdjI cGdGYdGe h GdYdGbGJ GdYGeI h GdOYGjI h GdOYGjI GdSjGSjI aVdG Yf GdJMce aj GdacQ h ZSjd GdOeGZ (B..(3hEPG cGf GdGYdGe aj JYQjag GdeMGjO jJUd HJRhjO GdfGS HGdeYdheGJ GdUMjMI ef CLd JfhjQ GdQCj GdYGe h JhYjJg EdG Cf GdGYdGe ef GdfGMjI GdJWHjbjI bO jSJNOe ddJCKjQ GdGfaYGdj h JWhjY GdfGS h JhLjgjge fMh gOa eYjf (B.s
Keywords: (3GdGJUGd GdLeGgjQjs; (3GdGYdGe s; (3GdJfejIs